Shape optimisation of cold roll formed sections considering effects of cold working - Qadir, S.J.; Nguyen, V.B.; Hajirasouliha, I.; Ceranic, B.; Tracada, E.; English, M.A. (Thin-walled structures, 2022)
The design development of new cold roll formed sections can lead to a significant reduction in material costs if the sections are optimised for strength performance considering the effect of shapes and change of material properties by cold working during the manufacturing process. In this paper, the buckling and ultimate strengths of cold roll formed channel and zed sections with intermediate stiffeners under distortional bending were studied using experimentally validated Finite Element (FE) models. The section strength was optimised using FE modelling and optimisation based on Design Of Experiments (DOE) and response surface methodology. A nonlinear FE model was first developed for a referenced section subject to four-point bending tests and the section’s dimensions and material properties were defined as geometric parameters using the DOE technique. A response surface was then used to determine the influences of the stiffeners’ location, shape, size, and cold working at the section corners and stiffener bends during the manufacturing process. A multi-objective genetic algorithm method was deployed to obtain optimal shapes for the sections with maximum buckling and ultimate strengths while keeping the same amount of material used. The results revealed that the ultimate bending moment capacities could be enhanced up to 17% and 25% for the channel and zed sections, respectively. Including the cold working effect had considerable enhancement in the ultimate moment capacities, with a maximum increase of 5%. The results of this study clearly demonstrated an efficient and effective approach to optimise design for strength performance of cold roll formed sections. •FE simulations of channel and zed sections were established and compared with test results.•FE models accounted for both geometric shapes and change of material properties due to cold working.•Strength of the sections were investigated by FE modelling integrated with design of experiments and response surface.•Optimal sections were achieved by using multi-objective genetic algorithm optimisation.